ANALISIS KEPADATAN JENTIK NYAMUK Aedes spp. DI PASAR TRADISIONAL KECAMATAN TALLO KOTA MAKASSAR - Widya Ifka; Suci Wulandhani; Ahmad Hasyim (Jurnal Inovasi Pendidikan dan Sains, 2021)
This study aims to determine the density of Aedes spp. larvae at the traditional market, Tallo District, Makassar City. This research is a type of descriptive research that describes the density of Aedes spp. larvae by conducting a limited characterization of the area which is the object of research. This research was conducted by taking samples of larvae in traditional markets in Tallo District, Makassar City and identifying samples at the Entomology Laboratory, Faculty of Mathematics and Natural Sciences, Hasanuddin University. The results showed that the larvae index obtained in the three traditional markets was included in the category of moderate risk of transmission because it was on a scale of 4 to 5, namely the CI value = 20.45% in Cidu Market, in Pannampu Market the CI value = 20.41% and the value of CI = 20.41%. CI = 11.11% in Paotere Fish Market. In conclusion, Aedes spp. was found living and breeding in the three traditional markets in Tallo District, Makassar City